Analysis of the Application of Information Technology in Improving the Efficiency of Supply Chain Management at JS Florist Store in Samarinda City - Jensi Norin Karapa; Muhammad Zaini; Rosyid Nurrohman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the application of information technology in improving the efficiency of supply chain management at JS Store Florist in Samarinda City. This study is motivated by the rapid development of information technology and its role in supporting supply chain management, especially for small-scale businesses. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, document study, and literature study. Data analysis was conducted using the SWOT analysis method. The results showed that the use of information technology can improve supply chain management efficiency, as seen from the savings in operating costs of IDR 1,300,000 per month, or equivalent to 17.21%. This proves that the application of information technology at JS Store Florist is capable of improving the efficiency of supply chain management. The use of marketplaces, digital recording, and online ordering strategies has been proven to accelerate production and distribution, as well as providing recommendations for the development of a more integrated digital ordering system to strengthen competitiveness and business sustainability in the face of increasingly fierce competition in the florist business.